The rhythm and tempo of the game of highly qualified teams - V'yacheslav Mulik; Victor Shalenko; Anatoliy Abdula; Andrii Pertsukhov (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to set indicators of rhythm and tempo of the game teams of high qualification. Material and Methods: analysis of the scientific-methodical literature, registration of technical-tactical actions, methods of mathematical statistics. The study of competitive activities was conducted with participating teams of world championship 2014. Results: the acticle shows indicators of the rhythm and tempo of the game of well-qualified teams. Conclusions: teams-winners have surpassed teams that concede in terms of indicators of passes the ball, shots at goal, the rhythm of the game, tempo of game.